Proliferation of myeloid lineage cells and apoptosis of lymphoblastic leukemic cells induced by short-course high-dose methylprednisolone in patients with acute lymphoblastic leukemia - Yıldıran, Alişan; Erduran, Erol; Tekelioğlu, Yavuz; Dilber, Embiya; Gedik, Yusuf (The Turkish Journal of Pediatrics, 2002)
In this paper, we investigated the effects of short-course high-dose methylprednisolone (HDMP) treatment on the proliferation of myeloid lineage cells and on apoptosis of blast cells in eight children with acute lymphoblastic leukemia (ALL). The patients were given the HDMP treatment (30 mg/kg/d, perorally) before 9:00 a.m. for seven days. Bone marrow (BM) aspiration was done at days 0 and 3 of the HDMP treatment in all patients and at the 7th day of the HDMP treatment in six patients. Bone marrow blast cells had gradually decreased after the HDMP treatment by the 7th day. There were statistically significant differences between the mean percentages of BM blast cells at days 0 and 3, days 0 and 7, and at days 3 and 7 (p
Keywords: acute lymphoblastic leukemia; short-course high-dose methylprednisolone; proliferation of myeloid lineage cells; apoptosis of lymphoblastic leukemic cells